2011
DOI: 10.1128/jb.05670-11
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Ureolytic Streptococcus salivarius Strain 57.I

Abstract: Streptococcus salivarius 57.I is one of the most abundant and highly ureolytic bacteria in the human mouth. It can utilize urea as the sole nitrogen source via the activity of urease. Complete genome sequencing of S. salivarius 57.I revealed a chromosome and a phage which are absent in strain SK126.Streptococcus salivarius, a member of the salivarius group of the viridans group streptococci, is one of the early colonizers of the epithelium and a common isolate of the human oral cavity (10). When S. salivarius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, not all S. salivarius strains possess the operon. Geng et al (2011) showed it to be absent in strain SK126, suggesting a recent loss of the operon from some strains within this species (perhaps reflecting the early stages of streamlining). The urease enzyme requires nickel to function ( Chen et al 1998 ), explaining the enrichment for nickel cation binding.…”
Section: Resultsmentioning
confidence: 97%
“…However, not all S. salivarius strains possess the operon. Geng et al (2011) showed it to be absent in strain SK126, suggesting a recent loss of the operon from some strains within this species (perhaps reflecting the early stages of streamlining). The urease enzyme requires nickel to function ( Chen et al 1998 ), explaining the enrichment for nickel cation binding.…”
Section: Resultsmentioning
confidence: 97%
“…Some contigs encoding dihydrofolate reductase and a mobilization element had high nucleotide identity to known commensals (e.g. F24TRSX_31, with >98% identity to Streptococcus salivarius (GenBank Accession CP002888.1)) [37] . Others were similar to pathogens: F30TRSX_13 had 99% identity to the Klebsiella pneumoniae plasmid pJIE137 (GenBank Accession EF219134), which is closely related to the p271a plasmid carrying the NDM-1 (New Delhi metallobetalactamase) that has been implicated in serious infections with carbapenem-resistant Gram-negative bacteria [38] .…”
Section: Resultsmentioning
confidence: 99%
“…The complete genome sequence of S. salivarius strain 57.I reveals a chromosome and a 40,758-bp plasmid, designated YMC-2011 (27). Most of the open reading frames (ORFs) annotated from YMC-2011 share significant homology with ORFs related to phage production, suggesting that strain 57.I is lysogenically infected with a temperate phage.…”
mentioning
confidence: 99%